THE EXPERT REVOLUTION: USING LEARNING TO ENGAGE AND COMPETE IN THE SKILLS WAR. Issue 91 (14th September 2018) - Palmer, Kelly; Blake, David
Abstract: Many managers and leaders, Palmer and Blake believe, have an outdated conception of organizational learning. They remind them that they "already have lots of experts in [their] workforce." They point to research from their own company, Degreed, and elsewhere about how employees learn not just from an organization's learning management system, but from "employees' self‐directed learning from all of the free, informal content that is available." A learning analytics model is described that allows companies to analyze data about how people are learning at four different levels: industry, company, organizational/team, and individual. It boils down to this: "Companies need to know if they have people with the skills that will take them into the future."